Methods for Finding the Offset in Robust Subspace Fitting. Issue 1 (18th November 2019) - Lellmann, Jan; Neumayer, Sebastian; Nimmer, Max; Steidl, Gabriele
Abstract: We propose a method for finding the offset in robust PCA which differs from the often used geometric median and arises in a natural way from maximizing the log‐likelihood estimator of a heavy‐tailed Student's t ‐distribution. Proof‐of‐concept numerical comparisons with other algorithms show the very good behavior of our approach.